George P. Merrill correspondence and autographs - Merrill, George P. (George Perkins), 1854-1929.
Autographs and letters of geologists and other scientists collected by Merrill while writing The First One Hundred Years of American Geology (1924). Includes letters addressed to James Hall, F.V. Hayden, and others. Correspondents include Cleveland Abbe, Louis Agassiz, Amos Binney, Thomas Cooper, Asa Gray, Clarence King, Robert E. Peary, Raphael Pumpelly, W.C. Redfield, Henry Rowe Schoolcraft, David Humphreys Storer, Eduard Suess, and John Torrey.
Smithsonian Institution.
Geologist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abbe, Cleveland, -- 1838-1916 -- Correspondence; Agassiz, Louis, -- 1807-1873 -- Correspondence; Binney, Amos, -- 1802-1878 -- Correspondence; Cooper, Thomas, -- 1759-1839 -- Correspondence; Gray, Asa, -- 1810-1888 -- Correspondence; Hall, James, -- 1811-1898 -- Correspondence; Hayden, F. V. -- 1829-1887 -- Correspondence; King, Clarence, -- 1842-1901 -- Correspondence; Peary, Robert E. -- 1856-1920 -- Correspondence; Pumpelly, Raphael, -- 1837-1923 -- Correspondence; Redfield, W. C. -- 1789-1857 -- Correspondence; Schoolcraft, Henry Rowe, -- 1793-1864 -- Correspondence; Storer, David Humphreys, -- 1804-1891 -- Correspondence; Suess, Eduard, -- 1831-1914 -- Correspondence; Torrey, John, -- 1796-1873 -- Correspondence; Geology; Geology -- United States; Science -- United States; Geologists